DIGITAL MARKETING: PENINGKATAN KAPASITAS DAN BRAND AWARENESS USAHA KECIL MENENGAH - Himawan, Abdurrahman Faris Indriya (Jurnal Analisis Bisnis Ekonomi, 2019)
Digitalization, especially social media has been claimed to change consumer behavior with important consequences for companies, product and brands. Consumers use online service to browse, store and play mucis, send email access Facebook, Twitter, Instagram and applications with various connected devices such as smartphone, tablet, and laptop ultimately change the way to use internet access not just for information but alsi for business. This research contributes to the understanding of SME marketing practices by using digital marketing in the marketing mix of SME in the Muhammadiyah Economy & Entreprneurship Council in the Gresik Regional (MEK PDM).